Students’ Cognitive, Affective, and Behavioural Perceptions of the Quizizz Towards Their Grammar Skills in a Business English Training Class at PT. Xl Axiata Tbk. Jakarta - Ligolita Putri Fatoni; Agus Santoso (Syntax Corporation Indonesia, 2024)
This study explored students’ perceptions of the Quizizz platform in a Business English training class at PT. XL Axiata Tbk. in Jakarta. To promote effective language learning, especially in a Business English training class, a dynamic and engaging teaching approach is essential. Traditional methods such as lectures and exercises often lack the enthusiasm necessary to actively involve students in the learning process. In incorporating game-based elements like rewards, rivalries, and instant feedback, gamification provides a potential solution to increase engagement and improve learning outcomes. The study utilized a mixed-methods design, gathering data through questionnaires, interviews, and documentation analysis. The sample included 47 students from a Business English training class at PT XL Axiata Tbk. Jakarta. The results showed that Quizizz, as a gamification platform, enhances student engagement and motivation in language learning and underscores the potential of gamification in language instruction, particularly within the context of a Business English training class.